DESIGNING SIGNAGE AND WAYFINDING AS INFORMATION FOR LAWANG SEWU - Noll, Patrecia Dwi Maharani; Ar Razi, Aria; Ayu, Intan Kusuma (Telkom University, 2024)
Historical Tourism in Indonesia is one of the things that is of interest to tourists. This is due to tourists' curiosity about history - history that occurred in the past. Then historical tourism is also important for visitors to increase their opinion of the surrounding area, and visitors can better appreciate the story behind it. One example is Lawang Sewu which is located in Semarang, Indonesia. This iconic structure, known as the